In vivo anti-inflammatory effect of saponin-enriched fraction from Agave brittoniana Trel subspecie brachypus - Yisel González-Madariaga; Yilka Mena-Linares; Dalys Martín-Monteagudo; Arianna Valido-Díaz; José Orestes Guerra-; Leisy Nieto-Reyes (Facultad de Farmacia, Universidad de Granada, 2021)
ABSTRACT Introduction: Agave brittoniana Trel species. subsp. brachypus is characterized by its high content of steroidal saponins and these metabolites have anti-inflammatory properties. However, no previous studies indicate that extracts rich in saponins from this species have anti-inflammatory effect in vivo models. Method: Steroidal saponins in n-butanolic extract were obtained from a hydroalcoholic extract of Agave brittoniana. Phytochemical studies were used to verify the saponins presence. Doses of 25, 50 and 100 mg/kg were used in the acute model of edema induced by carrageenan and in the chronic model of cotton pellet-induced granuloma. Five groups of six male Sprague-Dawley rats each were designed by each in vivo study: three groups for saponin-enriched fraction at different doses, a normal control group and a positive control, which was treated with indomethacin. The inhibition percentage of the inflammatory reaction was the major answer variable. Results: The acute model of carrageenan-induced rat paw edema indicated that the groups corresponding to the doses of 50 and 100 mg/kg of saponin-enriched fraction showed the highest percentages of inhibition, after three hours of treatment. According to the chronic model results, saponins-enriched butanolic extract showed anti-inflammatory activity by reducing the dry weight of the granuloma and increasing the inhibition percentage. Conclusions: Saponin-enriched fraction from Agave brittoniana T. subsp. brachypus, have an anti-inflammatory effect in acute and chronic experimental models.